2010
DOI: 10.1007/s00018-010-0344-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein folding and aggregation in bacteria

Abstract: Proteins might experience many conformational changes and interactions during their lifetimes, from their synthesis at ribosomes to their controlled degradation. Because, in most cases, only folded proteins are functional, protein folding in bacteria is tightly controlled genetically, transcriptionally, and at the protein sequence level. In addition, important cellular machinery assists the folding of polypeptides to avoid misfolding and ensure the attainment of functional structures. When these redundant prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 197 publications
(231 reference statements)
0
64
0
2
Order By: Relevance
“…Our results demonstrating that stable crystalline inclusions accrue in strains that harbor cry19A and orf2, expressed either in cis or trans, provide strong evidence that ORF2 functions primarily as a C-terminal crystallization domain, as is known for large Cry proteins. The evidence for this is that (i) the two proteins appear in approximately equimolar amounts when observed by acrylamide gel electrophoresis, a phenomenon unlikely to occur with typical chaperonins (20); (ii) the fusion Cry19A:ORF2 protein forms stable crystals; (iii) when fused in frame with the N-terminal region of Cry1C, the chimeric protein (Cry1Cn:ORF2) forms visible inclusions, even though these are unstable, in sporulating cells of strain 4Q7 (Fig. 3); and (iv) ORF2 shares a considerable level of identity with the C-terminal region of large Cry proteins (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Our results demonstrating that stable crystalline inclusions accrue in strains that harbor cry19A and orf2, expressed either in cis or trans, provide strong evidence that ORF2 functions primarily as a C-terminal crystallization domain, as is known for large Cry proteins. The evidence for this is that (i) the two proteins appear in approximately equimolar amounts when observed by acrylamide gel electrophoresis, a phenomenon unlikely to occur with typical chaperonins (20); (ii) the fusion Cry19A:ORF2 protein forms stable crystals; (iii) when fused in frame with the N-terminal region of Cry1C, the chimeric protein (Cry1Cn:ORF2) forms visible inclusions, even though these are unstable, in sporulating cells of strain 4Q7 (Fig. 3); and (iv) ORF2 shares a considerable level of identity with the C-terminal region of large Cry proteins (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Likely due to this and perhaps to ensure the existence of raw material for novel proteins, E. coli degrades certain fractions of proteins at all times (10,11). Finally, when protein degradation is impaired, E. coli cells are able to aggregate the misfolded proteins, making use of the exposed hydrophobic surfaces of the misfolded proteins that can interact with one another (12,13). Recent evidence suggests that the aggregation process is not energy free (14); thus, it likely is essential for proper cell functioning.…”
mentioning
confidence: 99%
“…It has previously been observed that IcsAPT-GFP fusions behave similarly to thermo-aggregating proteins whereby small randomly distributed aggregates form upon expression, which then coalesce into polar aggregates at the old pole (Rokney et al, 2009). The preference of aggregates to accumulate at the pole is due to the combined actions of nucleoid occlusion and asymmetrical aggregate inheritance during population expansion (Lindner et al, 2008;Rokney et al, 2009;Sabate et al, 2010;Winkler et al, 2010). Cytoplasmic chaperones such as DnaK are required for efficient protein disaggregation and polar aggregation, and have also been implicated in IcsA polarity determination (Calloni et al, 2012;Carrió & Villaverde, 2005;Castanie-Cornet et al, 2014;Janakiraman et al, 2009;Rokney et al, 2009;Saibil, 2013).…”
Section: Discussionmentioning
confidence: 99%